Principles of plant genetics and breeding - Acquaah, George (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
To respond to the increasing need to feed the world's population as well as an ever greater demand for a balanced and healthy diet there is a continuing need to produce improved new cultivars or varieties of plants, particularly crop plants
1. Overview and historical perspectives -- 2. Population and quantitative genetic principles -- 3. Reproductive systems -- 4. Germplasm for breeding -- 5. Breeding objectives -- 6. Selection methods -- 7. Molecular breeding -- 8. Marketing and societal issues in breeding -- 9. Breeding selected crops
Includes bibliographical references and index
Keywords: Plant breeding; Plant genetics